TRANSFERIBILIDADE DE MARCADORES MICROSSATÉLITES ENTRE ESPÉCIES DE ASTERACEAE E SUA UTILIDADE NA OBTENÇÃO DE DADOS GENÉTICOS-POPULACIONAIS - WEBER, GABRIELA GOMES (2016)
The Atlantic Forest is known for its biodiversity and at the same time, constitute one of the most degraded and fragmented biomes on the planet, these motives, which make part of the list of global biodiversity hostspots. This biome, particularly in the state of Paraná, consists of various vegetation types, such as Araucaria forest, which is usually associated with Campos. These transition regions, develop various plant species with high medicinal and ecological importance, most of them, of the Asteraceae family. However, little is known about the genetic-population characteristics of these species, which assesses the conservation status and risk of local extinction of the same. One way to perform this type of study is through molecular markers, including, microsatellites. However, there are still no specific primers for the vast majority of brazilian native species, making the transferability of microsatellite loci developed from phylogenetically related species, an alternative to this limitation. The transferability is a feasible and relatively inexpensive method that allows genetic research and population-preserving. In this sense, the objective of this study was to investigate the transferability of microsatellite markers among species of Asteraceae and evaluate its usefulness in obtaining population genetic data. For this, 15 pairs of microsatellite primers were selected from the literature and tested in five native species of Asteraceae from Atlantic Forest (Achyrocline flaccida (Weinm.) DC., Baccharis articulata (Lam.) Pers., Baccharis milleflora (Less.) DC ., Baccharis sp. and Senecio brasiliensis (Spreng.) Less). Subsequently, the polymorphic loci were evaluated for their ability to evidence-population genetic aspects of these species. The results of the transferability showed a 66.66% of amplification in A. flaccida, 66.66% in B. articulata, 40.0% in B. milleflora, 53.33% in B. sp. and 26.60% in S. brasiliensis. The results of evaluation of the usefulness of the primers showed low number of alleles (one to three) and low polymorphism. A high number of null alleles was identified and the statistical analyzes revealed low values of observed and expected heterozygosity. The data showed that the transferability of microsatellite primers is restricted in the evaluated species. However, transferability in Asteraceae varies widely, depending on many factors such as the phylogenetic distance between the species, the mutation rate of the loco, the effective population size, genetic drift and hence the conservation of regions flanking primers, among others. The data obtained in the evaluation of the usefulness of primers demonstrate that the high presence of null alleles prevents analysis of the population genetic structure of the species, for underestimating the polymorphism. Thus, the results obtained in our study showed that although the average rate of amplification in some populations, the microsatellite markers developed in Asteraceae and evaluated in this paper are not useful for genetic studies of A. flaccida (Weinm.) DC., B . articulata (Lam.) Pers., B. milleflora (Less.) DC., B. sp. and S. brasiliensis (Spreng.) Less.